The hepatocyte nuclear factor 1 homeobox A (HNF1A) gene polymorphism and AFP serum levels in Egyptian HCC patients - Hanan M. Bedair; Ibrahim El-Tantawy El Sayed; Olfat M. Hendy; Mohmed Abdel-Samiee; Islam Abd El Hamid El Sayad; Sally S. Mandour (Egyptian Liver Journal)
Abstract Background Hepatocyte nuclear factors were first identified as liver-enriched transcription factors that might participate in various activities related to the transcription of genes unique to the liver. Objective The study aimed to reveal the impact of HNF1A gene variations on disease progression in hepatocellular carcinoma (HCC) patients and its relation to serum alpha-fetoprotein level. Methods Participants in the study were classified as Group I, 32 HCC patients; Group II, 36 chronic hepatitis C patients; and Group III, 26 healthy volunteers as a control group. Each patient underwent full history taking, thorough clinical examination, and radiological examination. Furthermore, tumor staging was done using BCLC staging system. HNF1A gene polymorphisms (rs 2,464,196 and rs 1,169,310) were genotyped by real-time PCR. Results The findings revealed the highest frequency of AA and GA genotypes of HNF1A (rs2464196) polymorphism in both HCC (P = 0.002) and chronic HCV (P = 0.004) patients in comparison with controls. Regarding rs1169310gene polymorphism, no significant variation was observed across various genotypes when comparing the experimental groups to the control group. Additionally, HCC patients harboring the AA genotype for rs2464196 had significantly increased AFP (≥ 200 ng/ml) levels, whereas HCC patients with rs1169310 SNPs for HNF1A had no significant association regarding the AFP level. Conclusion The rs2464196 polymorphism of HNF1 is associated with increased AFP levels and HCC disease progression, which may be a prognostic and diagnostic genetic indicator.